Essential Oils: Chemistry and Pharmacological Activities - de Sousa, Damião P.; Damasceno, Renan Oliveira S.; Amorati, Riccardo; Elshabrawy, Hatem A.; de Castro, Ricardo D.; Bezerra, Daniel P.; Nunes, Vitória Regina V.; Gomes, Rebeca C.; Lima, Tamires C. (Biomolecules (Basel, Switzerland), 2023)
In this review, we provide an overview of the current understanding of the main mechanisms of pharmacological action of essential oils and their components in various biological systems. A brief introduction on essential oil chemistry is presented to better understand the relationship of chemical aspects with the bioactivity of these products. Next, the antioxidant, anti-inflammatory, antitumor, and antimicrobial activities are discussed. The mechanisms of action against various types of viruses are also addressed. The data show that the multiplicity of pharmacological properties of essential oils occurs due to the chemical diversity in their composition and their ability to interfere with biological processes at cellular and multicellular levels via interaction with various biological targets. Therefore, these natural products can be a promising source for the development of new drugs.